Food IQ : 100 questions, answers, and recipes to raise your cooking smarts - Holzman, Daniel; Rodbard, Matt (HarperWave, an imprint of HarperCollinsPublishers, 2022)
Two friends, one a food writer and one a chef, share their passion for cooking through one hundred essential cooking questions and answers, including "Why does pasta always taste better in a restaurant?" and "What is baker's math?"